Manuals on reading and national pacification during the recent post-conflict period in Colombia (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2017)
The teaching strategies used to consolidate post-conflict peace and pacification in Colombia after the last civil war (1899-1902), from a descriptive perspective and by comparing sources, allow us to recognize the role played by each book, each heroic or moral reading disseminated in the compulsory reading texts used in Colombian schools and colleges after 1902. To this end, the importance of public investment in the discourse of the victors, the emergence of religious publishers promoting censorship and content unification that promoted new readings and patriotic stories about Colombia, as well as the publishing efforts of the defeated after the Thousand Days' War, is demonstrated.